Clarification of the algorithm for estimating the frequency of the signal received by the satellite communication system in a continuous mode under the influence of «neighboring channels» - Turovsky, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2020)
Satellite communication systems that use phase modulation of a signal designed to transmit useful in formation in a continuous mode face the problem of frequency uncertainty of the signal when used as intended. For demodulators of satellite modems of such systems operating with a continuous input signal, the most significant is the problem of synchronization in the frequency of carrier oscillations in the conditions of frequency uncertainty of the signal. This synchronization task is actually reduced to estimating the true parameters of the signal, namely the estimation of the carrier frequency. The complexity of the task of estimating the carrier frequency in a satellite channel with phase modulation is exacerbated by the presence of additional interfering actions of "neighboring channels" - signals with the same type of modulation and the same data rate. The paper specifies the algorithm for estimating the carrier frequency of the signal receiv ed by the satellite communication system in a continuous mode, taking into account the influence of "neighboring channels" of information transmission. This algorithm allows to estimate the carrier frequency according to the rule of maximum likelihood, tak ing into account the condition of uncertainty of all parameters of the signal received by the satellite communication system in continuous mode, taking into account the in fluence of "neighboring channels" of information with a minimum observation interval. It includes the steps of: calculating the readings of the amplitude spectrum of the received signal and counting the convolution of the obtained amplitude spe ctrum with frequency response UV; calculating the count of the derivative convolution and finding the initial estimate of the frequency; based on the obtained evaluation of the evaluation procedure based on the multiplication of the phase of the received signal and the calculation of the estimated carrier frequency of the received signal.In order to assess the effectiveness of this algorithm in the comparison of the effectiveness of the estimates provided by the proposed procedure and the estimates made on the basis of subtraction of the global maximum convolution of the amplitude spectrum of the received signal. The results of this assessment presented in the paper showed that the dependences of the normalized variance on practically do not differ. That confirms the efficiency an d feasibility and practical value of the algorithm for estimating the carrier frequency given in the work, taking into account the influence of "neighboring channels" of useful signal transmission. A promising area for fu rther study of the issues raised in the work is the adaptation of this algorithm to the carrier frequency estimation in combined phase synchronization systems that have the ability to increase the order of astatism, monitoring the carrier frequency (pilot signal), the phase of which is modulated by a d eterministic Doppler signal.

Супутникові системи зв’язку, які використовують фазову модуляцію сигналу, що призначений для передачі корисної інформації в безперервному режимі, при застосуванні за призначенням стикаються з проблемою частотної невизначеності сигналу. Для демодуляторів супутникових модемів таких систем, що працюють з безперервним вхідним сигналом, найбільш значущою є проблема синхронізації по частоті несучого коливання в умовах частотної невизначеності сигналу. Вказане завдання синхронізації фактично зводиться до оцінки істинних параметрів сигналу, а саме оцінки несучої частоти. Складність завдання оцінки несучої частоти в супутниковому каналі з фазовою модуляцією усугубляється наявністю додаткових заважаючих дій «сусідніх каналів» –сигналів з тим же самим типом модуляції і тією ж швидкістю передачі інформації. В роботі уточнено алгоритм оцінки несучої частоти сигналу, що приймається супутниковою системою зв’язку в безперервному режимі з урахуванням впливу «сусідніх каналів» передачі інформації. Вказаний алгоритм дає змогу здійснити оцінку несучої частоти по правилу максимальної правдоподібності з врахуванням умови невизначеності всіх параметрів сигналу, що приймається супутниковою системою зв’язку в безперервному режимі з урахуванням впливу «сусідніх каналів» передачі інформації при мінімальному інтервалі спостереження. Він включає етапи: обчислення відліку амплітудного спектру сигналу, що приймається і відліку згортки отриманого амплітудного спектру з АЧХ УФ; обчислення відліку похідної згортки і знаходження первинної оцінки частоти; на основі отриманої оцінки проведення процедури оцінки, основаної на помноженні фазі сигналу, що приймається і обчислення оцінки несучої частоти сигналу, що приймається. З метою оцінки ефективності вказаного алгоритму в роботі проведено порівняння ефективності оцінок, забезпечених запропонованою процедурою і оцінок, здійснених на основі одрахування глобального максимуму згортки амплітудного спектру сигналу, що приймається. Подані в роботі результати вказаної оцінки показали, залежності нормованої дисперсії від практично не відрізняються. Що підтверджує ефективність та реалізуємість та практичну цінність поданого в роботі алгоритму оцінки несучої частоти з урахуванням впливу «сусідніх каналів» передачі корисного сигналу. Перспективним напрямком подальшого дослідження порушених в роботі питань є адаптація вказаного алгоритму до оцінки несучої частоти в комбінованих систем фазової синхронізації, що мають можливість до підвищення порядку астатизму, при стеженні за несучою частотою (пілот - сигналом), фаза якої модульована детермінованим допплерівським сигналом.
Уточнення алгоритму оцінки частоти сигналу, що приймається системою супутникового зв’язку в безперервному режимі при умові впливу «сусідніх каналів»
Keywords: fast Fourier transform function; функція швидкого перетворення Фур’є